A Comparative Study of Consumer Buying Behaviour: Price Perception of Grocery Products at D-Mart (Damani Mart) and Reliance Smart Bazar in Ahmedabad City - Kuldip, Chauhan; Divya, Parmar; Vidani, Jignesh (Contemporary Journal of Applied Sciences, 2024)
This study investigates consumer buying behavior in the grocery sector, comparing price preferences, store attributes, and shopping modes at D-Mart and Reliance Smart in Ahmedabad, India. The research examines age-related influences on price perception, promotional offers, online reverse in-store shopping, and trust in payment methods. Using a structured questionnaire and Chi-square tests, findings reveal no significant age impact on price perception or promotional influence but a notable association between age and trust in cash-on-delivery (COD) payment options, especially among older consumers. Store layout and product placement influenced all age groups, emphasizing the importance of an organized environment. The study highlights the need for customized marketing strategies and flexible payment options to enhance customer satisfaction and loyalty